Virus-induced opposite effect on Bombyx mori gene transcriptions - Y Yin; H Xia; F Zhu; L Chen; P Lü; K Chen (Invertebrate Survival Journal, 2016)
Bombyx mori bidensovirus (BmBDV) and Bombyx mori nucleopolyhedrovirus (BmNPV) are serious pathogens of Bombyx mori. In this study, we reported the changes of transcription level of several immune genes, including bmi, argo, dicer, cap1, cap3 and car, in Bombyx mori midgut after exposure to BmBDV or BmNPV. Silkworm strains 798 (anti-BmBDV) and 306 (susceptible to BmBDV) were subjected to BmBDV infection, and NB (anti-BmNPV) and HUABA (35) (susceptible to BmNPV) were subjected to BmNPV infection. The results showed that the transcription levels differ largely among different silkworm strains, and that the extent to which the gene transcriptions were affected by the viruses was different. However, both BmNPV and BmBDV viruses can reverse the transcription patterns of these genes when the silkworms were administered with the viruses compared with those control groups. The transcript levels of bmi and dicer were decreased in 798 and 306 strains that were inoculated with BmBDV compared with their respective controls, but were increased in NB and HUABA (35) inoculated with BmNPV. The transcript levels of argo and cap3 were risen in 798, 306 and NB strains when inoculated with their respective viruses, but were decreased in HUABA (35) strain. The transcript levels of cap1 were risen in all silkworm strains, while the levels of car were decreased in 798, 306 and HUABA (35) strains, and increased in NB strain when inoculated with their respective viruses. These findings may contribute to more in-depth understanding on functions of these genes in virus infection and proliferation.